The effect of acetylation phenotype on the dynamic changes of indices of calcium metabolism and iron levels in liver detoxification on the background of experimental hypothyroidism - Saidov, Saidamir; Ahmadjonuv, Asilbek; Mavlonov, Anvar (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Some studies of the characteristics of the calcium-phosphorus metabolism changes in experimental hypothyroidism given the phenotype of acetylation will allow to more effectively diagnose, predict the course and to carry out prevention and treatment of hypothyroidism and the accompanying pathological changes. The aim is to trace the dynamics of phosphorus-calcium metabolism and the level of serum iron in experimental hypothyroidism and to determine the severity of it changes depending on the type of acetylation. Methods: In experiments were used rats weighing 180-220g, who were divided into 2 main groups depending on the type of acetylation on α - slow and β - fast metabolizer (acetylators). Each group was modelled experimental hypothyroidism by the introduction of mercazolil at a dose of 5 mg, for 14 days. Each group was divided into 5 subgroups depending on the time of the study. Group of α-slow metabolizers (acetylators) were divided into the following subgroups: Iα - intact IIα - at the 4th hour of the study, IIIα - on the 1st week of the study, IVα - 2-week studies, Vα - on the 3rd week of the study. Results: In the study of the calcium concentration at the 4th hour of the study in subgroups with α - and β - acetylation phenotypes were observed the decrease by 12.0% and 10.5% respectively, and its level in the IIβ - subgroup was 5.3% lower than the IIα- subgroup. The concentration of calcium ions in Vα subgroup was lower than in the Iα sub-group was 12.0%, and the level of calcium in the blood serum of animals Vβ was lower compared to Iβ IIβ IIIβ Ivβ-90.9%, 72.7%, 80.0%, 80.9% respectively. Also relatively, Vα Vβ subgroups in the subgroup calcium concentration were lower at 81.8 percent. Conclusions: Belonging to a particular phenotype of acetylation affects the degree of severity of the changes of indices of calcium-phosphorus metabolism and serum iron in experimental hypothyroidism, the most significant differences between the values of their indicators were detected early and deadlines of the study.